2017
DOI: 10.14529/hsm170303
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Changes in Postural Balance of Vertical Position in Elite Taekwondo Practitioners Within a Full-Year Macrocycle

Abstract: 30Введение. Одним из практико-ориенти-рованных направлений психофизиологии яв-ляется диагностика, измерение и коррекция функциональных состояний, оценка расходо-вания резервов, что важно для сохранения здоровья и профессионального долголетия работников [8,12,14]. Риск-ориентированный подход для определения вероятности возник-новения негативных функциональных состоя-ний, позволяющих представить психофизио-логическую стоимость труда, в настоящее время получает широкое распространение в различных сферах профессио… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Greco-Roman wrestlers has shown that there is no unified approach to assessing the adaptive mechanisms of body energy systems at the pre-competition stage, which indicates the novelty of this study. Previously, performed works have shown the demand for the study of the control of heart rate variability in strength sports athletes [1], [2], [3], [4]; the control of biochemical parameters of athletes' training level by the example of weightlifters and martial arts athletes [5], [6]; the connection between heart rate and steroid hormones in their impact on muscle load [7], [8]; hormonal activity of testosterone and cortisol, and the effect of cortisol on the psych emotional state of strength sports athletes [8], [9], [10], [11], [12], [13]; control of thyroid-stimulating hormone during physical activity [14], [15]; and complex diagnostics of training level [16], [17], [18], [19], [20], [21].…”
Section: The Analysis Of Sports Training Of Qualifiedmentioning
confidence: 99%
“…Greco-Roman wrestlers has shown that there is no unified approach to assessing the adaptive mechanisms of body energy systems at the pre-competition stage, which indicates the novelty of this study. Previously, performed works have shown the demand for the study of the control of heart rate variability in strength sports athletes [1], [2], [3], [4]; the control of biochemical parameters of athletes' training level by the example of weightlifters and martial arts athletes [5], [6]; the connection between heart rate and steroid hormones in their impact on muscle load [7], [8]; hormonal activity of testosterone and cortisol, and the effect of cortisol on the psych emotional state of strength sports athletes [8], [9], [10], [11], [12], [13]; control of thyroid-stimulating hormone during physical activity [14], [15]; and complex diagnostics of training level [16], [17], [18], [19], [20], [21].…”
Section: The Analysis Of Sports Training Of Qualifiedmentioning
confidence: 99%
“…Longitudinal arch flattening weakens shock-absorbing functions of the foot, which increases shock effects on the knee and hip joints. This results in rapid fatigue and leads to pains in different body regions distal from the foot [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%